Endocrine disruptive action of diclofenac and caffeine on Astyanax altiparanae males (Teleostei: Characiformes: Characidae) - Godoi, Filipe G.A.; Muñoz-Peñuela, Marcela; Gomes, Aline D. Olio; Tolussi, Carlos E.; Brambila-Souza, Gabriela [UNESP]; Branco, Giovana S. [UNESP]; Lo Nostro, Fabiana L.; Moreira, Renata G. (Elsevier, 2020)
Diclofenac (DCF) and caffeine (CAF) are persistent pharmaceuticals that occur in mixtures in the aquatic ecosystems causing effects in the reproductive physiology of aquatic organisms. This study evaluated the physiological reproductive responses of Astyanax altiparanae males exposed to nominal concentrations of DCF (3.08 mg L− 1) and CAF (9.59 mg L− 1) separately and combined, for 96 h. The steroids profile, estrogenic biomarker vitellogenin (vtgA), testes and liver morphology, and also mortality of males were assessed. DCF and CAF degradation was 5% of the initial concentration for 24 h. The LC50 of the DCF and CAF were 30.8 mg L− 1 and 95.9 mg L− 1, respectively. Males exposed to DCF and CAF exhibited a reduction of 17β-Estradiol (E2) concentration compared to control (CTL). Similarly, testosterone (T) was also reduced in the DCF treatment, but this response was not observed in 11-Ketotestosterone (11-KT). Males exposed to DCF + CAF combined did not exhibit differences in T, E2 and 11-KT steroids. The vtgA gene expression and the sperm concentration did not change among the treatments. Moreover, acute exposure revealed a hypertrophy of hepatocytes cells in the DCF and DCF + CAF treatments. In conclusion, DCF and CAF, isolated, exhibit an endocrine disruptive activity in A. altiparanae male, an opposite response observed with the mixture of both compounds that abolishes the endocrine disruptive effects. DCF seems to be more toxic for this species, altering also hepatocytes morphology.
Keywords: Endocrine disrupting chemicals; Fish; Pharmaceuticals; Steroidogenesis; Vitellogenin a